Resilience in aging concepts, research, and outcomes - Resnick, Barbara; Gwyther, Lisa P.; Roberto, Karen A. (Springer, 2011)
Resilience in Aging Concepts, Research, and Outcomes Barbara Resnick, Karen A. Roberto, and Lisa P. Gwyther, editors While medical advances are prolonging the lives of countless older adults, longevity can come at a steep price, such as chronic pain, fatigue, depression, or cognitive decline. To meet this widespread challenge, resilience?the ability to meet and recover from setbacks?has emerged as a promising clinical strategy toward successful aging. The only book devoted solely to the importance and development of resilience in elders? quality of life, Resilience in Aging offers evidence-based theory, clinical guidelines, case examples, and real-world interventions so professional readers can make the best use of this powerful tool, whether one?s clients are in the office or in long-term care, in need of physical or psychological support, worried well or seriously ill. The books coverage extends across disciplines and domains, including: Cultural and ethnic perspectives on resilience in aging. ? Resilience on the job for the older worker. ? Resilience and personality disorders. ? Fostering resilience in chronic illness. Using the arts to promote resilience in persons with dementia. ? Policies to support resilience in an aging society. ? A resilience-building crisis response team. This wide-ranging lifespan approach gives Resilience in Aging particular relevance to the gamut of practitioners in elder care, including health psychologists, neuropsychologists, clinical psychologists, psychiatrists, social workers, geriatricians, family physicians, nurses, and occupational and physical therapists.